Prevalence of hemoglobinopathies in different regions and castes of Uttar Pradesh, India -A hospital based study - Verma, Pratima; Ghildiyal, Archna; Verma, Dileep; Krishna, Akhilesh; Singh, Shraddha; Kumar, Ashutosh; Tiwari, Sunita (Asian Journal of Medical Sciences, 2015)
Background: Thalasemia and other hemoglobinopathies are found in all the states of India and their prevalence is quite variable. In Uttar Pradesh very few studies are found which explore the spectrum of hemoglobinopathies. There is no such study which identifies the geographic distribution of high-risk communities with frequencies of hemoglobinopathies. Aim: Present study was carried out to determine the prevalence of hemoglobinopathies in different regions and castes of Uttar-Pradesh (UP) state. Materials and Methods: This is a preliminary community based cross-sectional, hospital based study, conducted at King George’s Medical University, Lucknow, Uttar- Pradesh. Subjects aged between 18 to 65 years were enrolled for sampling. The anticoagulated blood was used for performing CBC (complete blood count), and hemoglobin electrophoresis to measure hemoglobinopathies. Results: The present study revealed higher(28/194;19.5%,p<0.05) prevalence of hemoglobinopathies in Lucknow district as compared to other districts of Uttar-Pradesh and Brahmin caste having high frequency (33/112;29.5%) followed by Jaiswal (3/13;23.1%) and Arora (2/9;22.2%). Conclusion: The data regarding prevalence and distribution can be useful in prevention and management of various hemoglobinopathies which play a vital role in the hospital blood bank as well as in the formulation of transfusion policies. DOI: http://dx.doi.org/10.3126/ajms.v6i5.12339 Asian Journal of Medical Sciences Vol.6(5) 2015 21-25